The Role of Perceived Organizational Support (POS) and Innovative Work Behavior (IWB) on SMEs Performance with Organizational Trust as Mediation Variable - Wijaya, Elyzabeth (International Journal of Social and Management Studies, 2023)
This study aims to analyze the relationship between perceived organizational support (POS) and organizational trust, analyze the relationship between innovative work behavior (IWB) and organizational trust, analyze the relationship between perceived organizational support (POS) and performance, and analyze the relationship between innovative work behavior (IWB). ) on performance, analyzing the relationship between organizational trust variables and performance. This type of research is associative research, namely research that aims to determine the relationship between two or more variables. Each research indicator was measured using a Likert scale 1-5 point scale and the degree of agreement from strongly agree to strongly disagree. The analytical tool used in this study was SEM based on PLS (Partial Least Square,  the respondents of this study are 276 SME owners in Banten Indonesia. The results of the hypothesis test showed that The results of the hypothesis test show that the variable perceived organizational support (POS) has niot  significant effect on organizational trust, the innovative work behavior (IWB) variable has a positive and significant effect on organizational trust, the variable perceived organizational support (POS) has a positive and significant effect on performance, the innovative work behavior (IWB) variable has a positive and significant effect on performance, the organizational trust variable has not significant effect on SMEs performance. Innovative work behaviour has no significant effect on performance through organizational trust, organizational trustdoes not mediate the relationship between Innovative work behaviour and performance. Perceived organizational support has no significant effect on performance through organizational trust, organizational trust does not mediate the relationship between Perceived organizational support on performance